Socioscientific issue and digital comic in problem based learning enhances student ecoliteracy toward UNESCO Global Geopark conservation - Erika Rosdiana; Retno Dwi Suyanti; Binari Manurung (International Journal of Evaluation and Research in Education (IJERE), 2026)
The Toba Caldera region, designated as a UNESCO Global Geopark, requires continuous efforts to preserve its environment and strengthen the ecoliteracy of its community. This study investigated improvements in students’ ecoliteracy, including knowledge, environmental caring attitudes, and pro-environmental behaviors, through the use of problem based learning (PBL) integrated with geopark socioscientific issues (GSSI) presented in a digital comic (Comdigi) format. A total of 156 junior high school students in the Toba Caldera area participated in the study. A total of 78 students learned through direct instruction (DI), and 78 received PBL with GSSI in Comdigi. Ecoliteracy knowledge was measured using a 30-item test, while caring attitude and pro-environmental behavior were assessed using questionnaires with 15 items each. The results showed that PBL integrated with GSSI in Comdigi significantly outperformed DI in enhancing ecoliteracy knowledge 39.80%, caring attitudes 49.8% and in pro-environmental behaviors 12.50% with N-gain score of 0.71. These findings confirm that incorporating GSSI in a Comdigi based PBL model effectively strengthens students’ ecoliteracy related to the Toba Caldera UNESCO Global Geopark (TCUGGp).